The mediating effect of functional connectivity on the bipolar-psychosis continuum - Chang, Cleon (Nanyang Technological University, 2023)
Bipolar disorder is a debilitating mental illness that not only affects sufferers but also imposes significant social, economic, and familial burden. Symptoms of psychosis are common, and current research suggests that bipolar disorder and schizophrenia have overlaps in symptomatology and aetiology. However, the study of bipolar-psychosis continuum lacks investigation on enduring traits, as well as common neural correlates that potentially mediate between them. To this end, I attempt to investigate the association between bipolar traits, psychotic traits (perceptual aberration, physical anhedonia, social anhedonia), and resting-state functional connectivity (rsFC) networks. The UCLA dataset was used in this study, in which data from a total of 143 participants, including 104 healthy controls and 39 individuals with bipolar disorder was analysed. Pearson’s correlation, network based statistics and bootstrapped mediation analyses were conducted. Bipolar and psychotic traits were found to be positively correlated, and scores were higher in individuals with bipolar disorder than controls. 61 links significantly associated with bipolar trait scores were identified through fMRI scan, and were further separated into bipolar-positive networks (BPN) and bipolar-negative networks (BNN). The altered rsFC networks within the BNN were default mode-frontoparietal, ventral attention-somatomotor, and default mode-somatomotor. For BPN, only the frontoparietal-somatomotor was found to be altered. The findings suggest that rsFC plays a mediating role in the relationship between bipolar traits and two of the three dimensions of psychotic traits measured, namely, perceptual aberration and social anhedonia. Moving forward, more studies could be done to advance the field of psychiatry by finding neurobiological markers such as specific rsFC networks to possibly establish a stable measurement of bipolar phenotype.